Pengaruh Harga, Kualitas Produk Dan Promosi Social Media (Instagram) Terhadap Keputusan Pembelian Produk Di Arema FC Official Store Malang (Studi Kasus Pada Konsumen Arema FC Official Store) - Abidulloh, Moch. Zidan; Widarko, Agus; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze and explain the effect of price, product quality and Instagram social media promotion on product purchasing decisions at Arema FC Official Store Malang. The data analysis method in this study is quantitative data analysis using SPSS. The population of this study were consumers of Arema FC Official Store. The sampling technique used purposive sampling with the Malhotra formula and obtained 80 respondents. The results showed that the price variable had a significant effect on product purchasing decisions at the Official Store Arema FC Malang, the product quality variable had an insignificant effect on product purchasing decisions at the Official Store Arema FC Malang, and Instagram social media promotion had a significant effect on product purchasing decisions at the Official Store Arema FC Malang, and Instagram social media promotion had a significant effect on product purchasing decisions at the Official Store Arema FC Malang. Keywords: Price, Product Quality, Instagram Social Media Promotion and Product Purchasing Decisions